DESIGN AND PRACTICE OF FINANCIAL PERFORMANCE MEASUREMENT NOVELTY USING THE BALANCED SCORECARD METHOD - Harley Agustian As-Samawi; Sutoyo; Muhammad Saifrizal; Agustin Nurhayati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to determine the design of financial performance measurements using the Balanced Scorecard method in Computer and other Equipment sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2023 period. This research approach is a descriptive approach, where the descriptive approach is a research method carried out to collect data according to the actual situation, classify and analyze the data, make conclusions to create an objective picture of the situation. The type of data in this research is quantitative data, namely data in the form of explanations/statements in the form of numbers. The data collection technique for this research is a documentation technique on the BEI secondary data source. The results of this research show that the ASGR company shows that its financial performance has achieved good and effective performance in the VERY GOOD category.